Marco teórico: el modelo de formación permanente del profesorado de los centros de profesores y recursos en la Comunidad de Madrid (1995 - 2001) - Barrio de la Puente, José Luis (Revista Complutense de Educación, 2006)
In this article, it is analysed the model of life-long training for teachers proposed by the spanish Ministry of Education, culture and Sport. During the period which comprised the years 1995 up to 2001, this formative objective was developed within the so-called Training and Resources Centres For Teachers (TRCTs). At present, these centres are called Counselling and Support Centres for Teachers (CSCTs). The article above mentioned, begins with the description of the social context as a global frame, goes on wit the analysis of the main functions of TRCTs and the professional profile of counsellors. To finish, it is analysed the counselling style, the targets and tasks of counsellors and, as a closing, some proposals of constant improvement in the training processes for teachers.
Keywords: Global frame; training model; training process; life-long training; counselling; training centre; teacher and counsellor